Isolated tau leptons in events with large missing transverse momentum at HERA - Chekanov, S; Derrick, A; Krakauer, D; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; et al. (2004)
A search for events containing isolated tau leptons and large missing transverse momentum, not originating from the tau decay, has been performed with the ZEUS detector at the electron-proton collider HERA, using 130 pb -1 of integrated luminosity. A search was made for isolated tracks coming from hadronic tau decays. Observables based on the internal jet structure were exploited to discriminate between tau decays and quark- or gluon-induced jets. Three tau candidates were found, while 0.40 -0.13+0.12 were expected from Standard Model processes, such as charged current deep inelastic scattering and single W ±-boson production. To search for heavy-particle decays, a more restrictive selection was applied to isolate tau leptons produced together with a hadronic final state with high transverse momentum. Two candidate events survive, while 0.20±0.05 events are expected from Standard Model processes. © 2004 Published by Elsevier B.V.